DEVELOPMENT OF UNIVERSITY DIGITAL SKETCH-MAP BASED ON EXPERIENCES AND DIGITAL TRACES - Muqorrobin, Kiroomin; Yudhistira, Moch Rajendra; Pratama, Muhammad Ardhika Mulya; Hidayat, Muhammad Fahmi; Widarto, Widarto (Universitas Negeri Malang, 2018)
The main purpose of a university is education. However, in addition to the educational process, people who are active in the university environment will surely leave valuable moments or experiences, especially in places that are often visited or even places that leave unforgettable impressions. Even so, the lack of attention to the moments or experiences makes the moments easily forgotten, and not conveyed to future generations. Therefore, we developed a digital sketch-map using past photo data and the recollections of campus society, we also conduct investigations on the recollections we got using Falk's theory of ?making of meaning? in a museum. The purpose of this study is to develop a digital sketch-map to ease archiving and saves some memories of Universitas Negeri Malang?s societ